2006
DOI: 10.1002/ajh.20564
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Fas (CD95/APO‐1) positivity in patients with primary nodal diffuse large B‐cell lymphoma

Abstract: Fas (CD95/APO-1) is a protein that is mainly related to apoptosis of lymphoid cells. The increment of Fas expression is associated with long-term survival in various malignancies. However, there are limited studies regarding the effect of Fas expression on the course and prognosis of non-Hodgkin's lymphoma. The aim of this study was to investigate the significance of immunohistochemical Fas expression on the prognosis of nodal diffuse large Bcell lymphoma.A total of 63 patients with primary nodal diffuse large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
4
0
5
Order By: Relevance
“…FL, GCB and non-GCB DLBCL showed a heterogeneous expression of CD95, while a low expression was observed in BL. Concerning DLBCL, CD95 expression is associated with a favorable prognosis, reflecting in higher overall survival rates (27,28). Similarly to the results found in this study, Nguyen and colleagues (1996) observed that lowgrade lymphomas, as FL, expressed CD95 more intensively when compared to high-grade lymphomas, as BL (29).…”
Section: Gcb Dlbclsupporting
confidence: 83%
See 1 more Smart Citation
“…FL, GCB and non-GCB DLBCL showed a heterogeneous expression of CD95, while a low expression was observed in BL. Concerning DLBCL, CD95 expression is associated with a favorable prognosis, reflecting in higher overall survival rates (27,28). Similarly to the results found in this study, Nguyen and colleagues (1996) observed that lowgrade lymphomas, as FL, expressed CD95 more intensively when compared to high-grade lymphomas, as BL (29).…”
Section: Gcb Dlbclsupporting
confidence: 83%
“…Concerning DLBCL, CD95 expression is associated with a favorable prognosis, reflecting in higher overall survival rates (27,28). Concerning DLBCL, CD95 expression is associated with a favorable prognosis, reflecting in higher overall survival rates (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99 This is likely owing to the fact that CD95 is often downregulated during tumor progression because cancer cells need to lower the risk of undergoing apoptosis while benefiting from CD95's tumorigenic activities. Occasionally, CD95L was also described as a positive prognostic marker for cancer.…”
Section: Other Activities Of the Apoptosis-inducing Receptor Cd95mentioning
confidence: 99%
“…in negative selection) 1,2 and in the termination of the immune response 3 . Fas is considered also to play a role in tumour formation, progression, and immunity 4–7 as well as in tumour responses to anticancer drugs 8,9 . Fas is expressed both in lymphoid and non‐lymphoid normal and malignant tissues.…”
Section: Introductionmentioning
confidence: 99%